Specificities of Sanfilippo A syndrome laboratory diagnostics - Trofimova, N.S.; Olkhovich, N.V.; Gorovenko, N.G. (Вiopolymers and Cell, 2014)
Mucopolysaccharidosis type IIIA (MPS IIIA) occurs due to the deficiency of lysosomal enzyme heparan-N-sulfatase (sulfamidase), which is caused by mutations in the SGSH gene. Aim. To identify the characteristics of biochemical diagnosis of MPS IIIA and determine the prevalence of major mutations R74C and R245H in the SGSH gene in Ukrainian patients. Methods. After all the required phases of laboratory diagnosis of this disease, the diagnosis of MPS IIIA was confirmed in 12 patients from 12 families. The level of sulfamidase activity in leukocytes did not exceed 36 % of the control in all patients. Due to very low sulfamidase activity in leukocytes it is sometimes difficult to interpret the results of the analysis which may lead to false-negative or false-positive diagnosis of MPS IIIA. Results. The analysis of the results of molecular investigation of the patients' samples showed that the incidence of mutation R74C was 17/24 (70.8 %), the incidence of mutation R245H was 2/24 (8.3 %). The total incidence of major mutations R74S and R245H among the patients with MPS IIIA in Ukraine was the highest among European countries – 11 out of 12 patients, these mutations were found in at least one allele. Conclusions. Given very high prevalence of major mutations R74S and R245H in the SGSH gene among the patients with MPS IIIA in Ukraine – 79.1 % – it is appropriate to have the screening of mutations in the diagnostic algorithm along with the definition of biochemical sulfamidase activity to prevent false-negative or false-positive diagnosis of Sanfilippo syndrome A.